If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x+3)-2(5x+1)=34
We move all terms to the left:
4(x+3)-2(5x+1)-(34)=0
We multiply parentheses
4x-10x+12-2-34=0
We add all the numbers together, and all the variables
-6x-24=0
We move all terms containing x to the left, all other terms to the right
-6x=24
x=24/-6
x=-4
| 6x^2-24x-9=0 | | (5x+10)-90-90=360 | | -5+4y+2y=3y-11+y | | 1+y/2=-2(y+1) | | (5x+10)-90+90=360 | | 1x+16=5x | | 109=65+.80m | | (5x+10)-90-270=360 | | 3/5p=5 | | (5x+10)-90-135=360 | | (5x+10)+90-135=360 | | 4=+8p-6p-5+20p | | (5x+10)-135+135=360 | | -6s=72 | | -2(-5y+9)=8(y-1) | | (5x+10)-90+135=360 | | 80+65a=85a | | (5x+10)+270-135=360 | | 4=b+8/7 | | (5x+10)-270+135=360 | | 21=-7(a-4) | | 2+(3–x)=8−2x | | (5x+10)-270+90=360 | | -4s=63 | | 3m+18=-21 | | 1x+13+1x=1x+13+1x | | (5x+10)+135-90=360 | | 5n+40=20 | | (5x+10)-170+90=360 | | (5x+10)-135+90=360 | | Y=15x+82 | | x^2+18x-2x^2+60=17 |